'Bürgerbewgung in der DDR während der Wende'. Interview mit Schwabe, 2-12-1992 und mit Sello, 2-5-1993 - Schwabe, Uwe.
'Bürgerbewgung in der DDR während der Wende'. Interview mit Schwabe, 2-12-1992 und mit Sello, 2-5-1993.